2021
DOI: 10.1021/acs.jpca.1c02794
|View full text |Cite
|
Sign up to set email alerts
|

Acene-Linked Zethrenes and Bisphenalenyls: A DFT Search for Organic Tetraradicals

Abstract: Polycyclic aromatic hydrocarbons are of special interest due to their promising nonlinear optical and magnetic properties. A series of acene-linked zethrenes and bisphenalenyls comprising from five to nine benzene rings in the linker group have been computationally studied by the DFT UB3LYP/6-311++G­(d,p) quantum-chemical modeling of their electronic structure, possible spin states, and exchange interactions. The zethrenes with octacene and nonacene linkers as well as bisphenalenyls comprising heptacene, octac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 119 publications
0
11
0
Order By: Relevance
“…In an attempt to extend the range of the exchange energies, we design the "double-arrow systems", denoted as [n] x,y -arrow, to modulate the interaction between two [n]-TG terminals by inserting a rectangular NG bridge 43,44 with its armchair edge length and zigzag edge width involving x and y hexagons, respectively, e.g., [4] 2,3 -arrow as shown in Scheme 2b. 45,46 For all double-arrow systems considered in this study, a spin-polarized BS ground state is observed. The relative energies for the low-lying spin states of the double-arrow systems with various terminal and bridge sizes are presented in Table S3.…”
Section: ■ Methodsmentioning
confidence: 99%
“…In an attempt to extend the range of the exchange energies, we design the "double-arrow systems", denoted as [n] x,y -arrow, to modulate the interaction between two [n]-TG terminals by inserting a rectangular NG bridge 43,44 with its armchair edge length and zigzag edge width involving x and y hexagons, respectively, e.g., [4] 2,3 -arrow as shown in Scheme 2b. 45,46 For all double-arrow systems considered in this study, a spin-polarized BS ground state is observed. The relative energies for the low-lying spin states of the double-arrow systems with various terminal and bridge sizes are presented in Table S3.…”
Section: ■ Methodsmentioning
confidence: 99%
“…A different class of conjugated polymers with alternating donor–acceptor units show below 1 eV gaps with strong diradical characteristics . The diradical character can be correlated to singlet fission reactions, , electronic properties of an open-shell system such as two photon absorptions, , excitation energies and singlet-triplet energy gaps, , and the optical properties such as hyperpolarizability and magnetic properties. , A neutral molecule with two unpaired electrons, with strong localization, results in diradicals as illustrated in Figure . Among the various mechanisms of diradical state stabilization, oligomers in this article achieve their singlet diradical character due to the repulsion of electrons with α and β spins.…”
Section: Introductionmentioning
confidence: 99%
“…23–29 Irrespective of the level of theory, wave function-based theory or density functional theory (WFT and DFT, respectively) calculations, such an approximation is considered to be satisfactory for molecular crystals and more questionable in covalent dimers. 30–34…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25][26][27][28][29] Irrespective of the level of theory, wave function-based theory or density functional theory (WFT and DFT, respectively) calculations, such an approximation is considered to be satisfactory for molecular crystals and more questionable in covalent dimers. [30][31][32][33][34] However, one may wonder how much the immediate environment of a given monomer may modulate its spectroscopy. In the design of singlet fission compounds, we felt that attention should be paid to the molecular description, and to go beyond the free monomer description.…”
Section: Introductionmentioning
confidence: 99%